Desvendando a matemática aplicada à rotulagem de alimentos - LISBÔA, Laís Ribeiro Corrêa (2023)
Nutritional practices are above all a pedagogical act of education. And in this context there is a need for interdisciplinary practices emanating from social realities, such as those expressed in food labeling in several areas. In this research interdisciplinarity has as its generating theme the food labeling and the expressions of basic mathematical functions expressed in this one. Thus, the objective of this research was to promote the description of the basic mathematical functions present in food labeling. The methodological bases followed researches in the main data bases of academic researches. The results show interdisciplinary constructions that begin in the relationship between nutrition and mathematics, and few with a focus on nutritional labeling and functions. Thus, this research seeks to evidence the possibility of applying nutritional concepts, specifically the labeling of foods as a generative theme for interdisciplinary practices with the bases of some mathematical notions.